If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a = 5a + 5a Combine like terms: 5a + 5a = 10a 7a = 10a Solving 7a = 10a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-10a' to each side of the equation. 7a + -10a = 10a + -10a Combine like terms: 7a + -10a = -3a -3a = 10a + -10a Combine like terms: 10a + -10a = 0 -3a = 0 Divide each side by '-3'. a = 0 Simplifying a = 0
| 12m=12m+3 | | x^2-2xy+y^2-10x-6y+25=0 | | 6t-8=16 | | p+11=0.3p+88 | | 8(9x-3)=264 | | 20x-2x=30 | | 500+3t=t+820 | | x+5=-23-4x | | 3(x-6)-(10-x)=30 | | 2/3(-6)=x | | -10x+1=2x-17 | | 8j+10=c | | 3x+5=-23-4x | | 4+6r-3=8r+10-5r | | 20m+1.7=30m+0.5 | | 4+6r-3=8r | | 1.8+w=3w+0.6 | | x=-4.9x^2+34.3x+1.5 | | 5(2x+7)=65 | | 9(x+6)=90 | | 44=22-5c | | 7q+9=9b^2 | | 2(x+y)+3(x+2y)= | | 7(x-1)=35 | | 0.8t+40=1.1t+10 | | -2(-9m-2)-1=21+10m | | 7n-4=14+n | | 5x+8=-62-5x | | 13y=0 | | 4s^2+28s+49=60 | | 10x+73=8x+191 | | -20=15s |